Rogowski Coil Sensor For Partial Discharge Detection - Murugaiah, Puovin (Universiti Sains Malaysia, 2018)
The term partial discharge refers to the partial breakdown of insulation that develops in zones of highly concentrated electric fields. So, to prevent the breakdown occurs frequent observations must be done by utilising precise detection methods. The measurement of this kind of discharges is of importance because its existence is related to the aging of insulation in electric equipment. Partial discharge (PD) test is normally used to evaluate the insulation quality of high-voltage equipment. There are many PD detectors available in the market, and the detectors employ many techniques in measuring the PD. This paper presents a simplified and low cost device PD detection system with the use of the Rogowski coil (RC). The high frequency pulses due to the PD are detected by the RC. RC is developed for high frequency range from one MHz up to order of hundred MHz’s. An experimental analysis is performed to evaluate Rogowski coil performance and the effect of designed circuit on output waveform of RC sensor for PD detection. The experimental set-up is arranged in high voltage laboratory. The tests are carried out concerning measurement conditions such as on-line PD measuring systems. Input PD signal generated by pulse generator is passed through the centre of RC where the output of it is already connected to the designed circuit. The measurement is made by using oscilloscope to capture the output waveform. The circuit design is done to improve the RC output for better detection system as well as to obtain the signal that is replicates the input PD signal. From the experiment it is investigated that this RC detection method works linearly and with high sensitivity to the lowest input (5pC).